Chronic Thromboembolic Pulmonary Hypertension – What Have We Learned From Large Animal Models - Stam, Kelly; Clauss, Sebastian; Taverne, Yannick J. H. J.; Merkus, Daphne (Frontiers in Cardiovascular Medicine, 2021)
Chronic thrombo-embolic pulmonary hypertension (CTEPH) develops in a subset of patients after acute pulmonary embolism. In CTEPH, pulmonary vascular resistance, which is initially elevated due to the obstructions in the larger pulmonary arteries, is further increased by pulmonary microvascular remodeling. The increased afterload of the right ventricle (RV) leads to RV dilation and hypertrophy. This RV remodeling predisposes to arrhythmogenesis and RV failure. Yet, mechanisms involved in pulmonary microvascular remodeling, processes underlying the RV structural and functional adaptability in CTEPH as well as determinants of the susceptibility to arrhythmias such as atrial fibrillation in the context of CTEPH remain incompletely understood. Several large animal models with critical clinical features of human CTEPH and subsequent RV remodeling have relatively recently been developed. In this review we will discuss the current knowledge on the processes underlying development and progression of CTEPH, and on how animal models can help enlarge understanding of these processes.